Community dynamics of anaerobic bacteria in deep petroleum reservoirs - Hallman, Christian; Schwark, L.; Grice, Kliti (Nature Publishing Group, 2008)
The nature, activity and metabolism of microbes that inhabit the deep subsurface environment are a matter of ongoing debate1?7. Primarily limited by temperature8, little is known about secondary factors that restrict or enhance microbial activity9,10 or about the extent of a habitable environment deep below the surface. In particular, the degraders of chemically inert organic substrates remain elusive9. Petroleum reservoirs can be regarded as natural bioreactors and are ideally suited for the study of microbial metabolism in the deep subsurface. Here we analyse series of oil samples that were biodegraded to different degrees. We find fatty acids after hydrolysis of purified crude oil fractions, indicating the presence of intact phospholipids and suggesting that indigenous bacteria inhabit petroleum reservoirs in sediment depths of up to 2,000 m. A major change in bacterial community structure occurs after the removal of n-alkanes, indicating that more than one consortium is responsible for petroleum degradation11. Our results suggest that further study of petroleum fluids will help understand bacterial metabolism and diversity in this habitat of the deep subsurface.